The Processing of Information According to the Linguistic Neural Programming and its Relation to the Level of Skills Performance of the Monument and Undermine the Scout Tent - Aqeel Yahya Hashim Abdulaziz (Journal of Global Pharma Technology, 2017)
Recently, the interest of trainers and teachers has increased to study the mental and physiological aspects of the player and the learner. The interest in the study of information processing and treatment levels has been highlighted as being one of the types of learning that has to do with the learner himself, directing and self-driving towards learning, and there is a close link between the representative systems owned by the learner whether (audio, visual, sensory) and the level of information processing on the one hand and between these systems and the level of learning skill on the other hand, the problem of this research is that there is a fluctuation among the students in the performance of the skills of erecting and undermining the scout tent. This may be due to the difference in their representation systems of the linguistic programming of the nervous system (auditory, visual and sensory) and related to the process of information processing within the brain.The researchers followed the following steps in the research procedures:The descriptive approach was used in the method of interconnectivity.The research was conducted on the students of the first stage in the Department of Physical Education College of Education for Girls - University of Kufa for the academic year 2016-2017 The sample (30)The sample was divided according to the Neural programming test into three groups representing the first group (the auditory system), the second group represented the visual system and the third group represented the sensory system.The research requires the use of several tests included the followingInformation processing test.Testing neural programming for representative systems (auditory, visual, and sensory).Skill tests of skill (erecting the tent, undermining the tent).The results of the researchThe level of information processing and accurate performance of the skill of setting the tent for those with the visual system is better than the audio and sensory system.The level of processing information undermines the tent for people with a visual system better than the system of audio and sensory.The processing of information is an important and essential role for the people of the visual system and the performance of the skills of the monument and undermines the tent.Keywords: Information Processing, Neural programming, Monument and undermine the scout tent.